Prospective Randomized Trial Comparing Buttressed versus Nonbuttressed Stapling in Patients Undergoing Pulmonary Lobectomy - Takamochi, Kazuya; Oh, Shiaki; Miyasaka, Yoshikazu; Matsunaga, Takeshi; Kitamura, Yoshitaka; Fukui, Mariko; Suzuki, Kenji (The Thoracic and Cardiovascular Surgeon, 2014)
Background The aim of this study was to evaluate the efficacy of buttressed stapling using a stapler with an attached polyglycolic acid sheet in reducing the rate of air leak associated with pulmonary lobectomy.Materials and Methods A prospective, randomized, phase III study was conducted to confirm the superiority of a buttressed stapler in a test treatment group to a conventional nonbuttressed stapler in a current international standard of care group among patients undergoing pulmonary lobectomy. The primary end point was the frequency of intraoperative air leaks.Results Although no fatal postoperative bleeding occurred in the present study, this trial closed early with 100 patients because the manufacturer recalled the buttressed stapler based on reports of 13 serious injuries and 3 fatalities following pulmonary resection in routine clinical practice. A total of 76 patients treated with a stapler (35 in the non-B group and 41 in the B group) were included as subjects in the analysis. No statistical differences were observed between the groups in the frequency of intraoperative air leaks (22 [63%] vs. 26 [63%]) or the postoperative duration of air leaks (mean: 3.5 vs. 2.9 days). The frequency of air leak from stapler holes was significantly lower in the B group than in the non-B group (2% [1/41] vs. 20% [7/35]; p = 0.016).Conclusions The efficacy of buttressed stapling in reducing the rate of air leak in patients undergoing pulmonary lobectomy could not be clearly demonstrated. However, air leak from stapler holes can be prevented with buttressed stapling.
Keywords: lung cancer treatment; surgery; complications; surgical equipment